Carmen Christi Philippians ii. 5-11 in recent interpretation and in the setting of early Christian worship - Martin, Ralph Philip (Grand Rapids, MI Eerdmans, 1983)
Includes bibliographical references and indexes.
Reprint. Originally published : London, UK : Cambridge UP, 1967
Keywords: Bible. N.T. Philippians II, 5-11 -- criticism, interpretation, etc